Programa educativo de comunicación asertiva para el mejoramiento de las relaciones interpersonales en directivos de tres instituciones públicas del nivel secundario área urbana San Juan Bautista 2023 - Noriega Soria, Damaris (2025)
The main purpose of this research was to evaluate how the assertive communication program influenced the strengthening of relationships among the principals of three public institutions located in the urban area of San Juan Bautista during the year 2023. In order to approach the study with rigor, an evaluative approach was adopted, adopting a research design that combines a field study, longitudinal, univariate and pre-experimental, with a single group. The study population consisted of 30 managers, including assistant directors, coordinators and workshop managers, and a sample of the same size was used. For the collection of information, a specialized survey presenting real cases was designed and validated by a panel of experts in the field. The mean values and standard variations of social interactions and their components in the administrators of three public high schools in San Juan Bautista reveal significant improvements after the implementation of the educational program. Favorable differences are observed in the averages, with an overall increase in the variable interpersonal relations from 78.00 to 105.77. The dimensions also show progress: abilities to cooperate increased from 16.50 to 24.06, empathic communication from 20.17 to 28.63, attitudes from 20.77 to 28.07, and treatment of managers from 21.07 to 25.10. These results demonstrate the positive effect of the program on interpersonal relationships.